Distribution and Morphological Description of Eumenes Mediterraneus (Kriechbaumer, 1879) in the Southern Fergana Region - ugli, Adkhamjon Rasuljonov Zokhidjon; Qobiljonovna, Shoxistaxon Yuldasheva; Rustamjonovna, Nigoraxon Zakirova (American Journal of Botany and Bioengineering, 2024)
This article provides information on the distribution and morphological characteristics of the species Eumenes mediterraneus (Kriechbaumer, 1879) in the Southern Fergana region. This species is a solitary wasp. The research was conducted in various ecosystems of Southern Fergana during 2023-2024. The ecological and morphological features, as well as the habitats of E. mediterraneus, have not been studied in this region. Therefore, this article presents some information about the distribution, morphological characteristics, and ecological role of E. mediterraneus wasp in the Southern Fergana area.